1984
DOI: 10.1002/app.1984.070291115
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding in epoxy resin/poly(ε-caprolactone) blends

Abstract: SynopsisPoly(ccapro1actone) (PCL) of ca. 20,000 molecular weight is shown to be partially miscible with three aromatic-amine-cured epoxy resins. This conclusion is based on the depression of the epoxy T,, the effect on physical and mechanical properties, and the observation that a large proportion (40-55%) of the PCL ester groups are involved in hydrogen bonding. This miscibility behavior is compared to PCL blends with anhydride-cured epoxy resins, which appear to have a two-phase morphology. The different mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 0 publications
4
44
0
Order By: Relevance
“…The reduction of the hydrogen-bonded carbonyl may be in part associated with the occurrence of phase separation after gelation resulting in fewer opportunities for interaction. 16 This statement can be confirmed by DSC results, which will be discussed subsequently. The melting behavior of polycaprolactone is evident in the cured polybenzoxazine blends with a PCL concentration higher than 11 wt %, indicating the occurrence of the macrophase separation.…”
Section: Hydrogen Bonding Of Carbonyl Groups From Pclsupporting
confidence: 72%
See 4 more Smart Citations
“…The reduction of the hydrogen-bonded carbonyl may be in part associated with the occurrence of phase separation after gelation resulting in fewer opportunities for interaction. 16 This statement can be confirmed by DSC results, which will be discussed subsequently. The melting behavior of polycaprolactone is evident in the cured polybenzoxazine blends with a PCL concentration higher than 11 wt %, indicating the occurrence of the macrophase separation.…”
Section: Hydrogen Bonding Of Carbonyl Groups From Pclsupporting
confidence: 72%
“…As seen in Figure 4, a much greater frequency shift (⌬) between the hydrogen-bonded and non-hydrogen-bonded carbonyl bands is exhibited in the blend with 6 wt % of PCL, indicating that the strength of the intermolecular hydrogen bonding between the carbonyl groups of PCL and the hydroxyl groups of poly(BA-a) is stiffer in the presence of lower amounts of the modifier. Moreover, the percentage of hydrogen bonding and the frequency shift (⌬) after curing isothermally at 180°C for 5 h are considerably lower than the maximum in all of the compositions, which is indicative of a much weaker hydrogen-bonding strength in the two-phase structure, whereas, in comparison with other reported data, the hydrogen-bonding strength in the PCL/benzoxazine blends (⌬ ϭ 22-25 cm Ϫ1 ) is slightly higher than in the PCL/ novolac (⌬ ϭ 20 cm Ϫ1 ), 22 PCL/epoxy (⌬ ϭ 17 cm Ϫ1 ), 16 and PCL/phenoxy blends (⌬ ϭ 15 cm Ϫ1 ). 20 It is suggested that a rather strong intermolecular hydrogen bond exists between PCL and poly(BA-a) even after the dramatic recovery resulting from the phase separation.…”
Section: Hydrogen Bonding Of Carbonyl Groups From Pclmentioning
confidence: 43%
See 3 more Smart Citations